Difficulties and practices regarding information provision among Korean and Italian nurses. (29th May 2017) - Ingravallo, F.; Kim, K.H.; Han, Y.H.; Volta, A.; Chiari, P.; Taddia, P.; Kim, J.S.
Abstract : Aim: To investigate nurses' opinions and practices of providing information in a global context through cultural comparison. Background and Introduction: Providing sufficient information to patients about nursing interventions and plans is essential for patient‐centred care. While many countries have specific legislation making information delivery to patients a legal duty of nurses, no such legislation exists in both the Republic of Korea and Italy; nurses' only guidance is the deontological code. Methods: This was a cross‐sectional survey study involving a convenience sample of 174 Korean nurses and 121 Italian nurses working in internal medicine and surgery at university hospitals. Data were collected using a self‐administered questionnaire between February and November 2014. The questionnaire assessed demographic and professional characteristics, and difficulties and practices regarding information provision. Results: Korean and Italian nurses significantly differed in all demographic and professional characteristics. More Korean than Italian participants reported that their role in providing information was well explained within their teams, but both groups reported the same level and type of difficulties in delivering information. Nurses in both countries regularly informed patients about medications and nursing procedures, but provided information about nursing care plans less frequently. Few nurses frequently provided information to relatives instead of patients. Conclusions: Despite cultural, demographic and professional differences between Korean and Italian nurses, their difficulties and practices in information delivery to patient were similar. Implications for nursing and health policy: Hospital managers and policymakers should be aware that nurse–patient communication can be impaired by organizational factors, patient characteristics or the interaction among providers. Educational interventions and strategies are needed to increase information provision to patients about nursing care plans.